[Gábor Radnai 5]
in the garden, stew-pot, boys playing, football, bicycle, ships& the Danube, Margaret-island, open-air cinema, International Fair in Budapest, Gellért-mountain& the town, skating on the Lake "Feneketlen", walking the dog, boy with pressure-well, guitar, old tape-recorder, dogs&photos, family walking, boy & schoolbag, students record, at the Lake Balaton, trabant, Móricz Zsigmond Square, at the Citadella, playing-ground, military boat & air show, walking at the Lake "Feneketlen", ducks, walking in the forrest